The Influence of Self Efficacy and Competence on Job Readiness Through on The Job Training For Students Majoring in Housekeeping Mediteranean Bali Bangli Campus - Ni Putu Krisna Purnama Sari; Hesty Prima Rini (PT. Publikasiku Academic Solution, 2023)
This study aims to determine the effect of self-efficacy and competence on Work Readiness through On the Job Training on housekeeping students of Mediteranean Bali Bangli Campus. This research is a quantitative descriptive research. The population and sample used were 60 housekeeping students of Mediteranean Bali Bangli Campus using the Total Sampling technique. This study used a Partial Least Square (PLS) as analysis tool. The results showed that self-efficacy and competence had a positive and significant effect on the work readiness of housekeeping students of Mediteranean Bali Bangli Campus. Then, self-efficacy and competence through on the job training also have a positive and significant effect on work readiness of housekeeping students of Mediteranean Bali Bangli Campus.